R&D and Aggregate Fluctuations - Pourpourides, Panayiotis M.; Artuc, Erhan (World Bank, Washington, DC, 2014)
The research and development (R&D) sector is considered one of the main driving forces of sustainable growth in the long run. The sector, however, also shows excessive volatility which raises interesting questions regarding the sources of this volatility as well as the nature of the relation between the sector and aggregate fluctuations. Using data from the United States Bureau of Economic Analysis and National Science Foundation, we show that technology innovations are the main source of fluctuations in R&D investment while R&D technology shocks are important in driving aggregate output fluctuations. After taking nominal innovations into consideration, such as shocks in monetary policy and inflation, capital investment-specific shocks explain 70 percent of fluctuations of R&D investment, while R&D technology shocks explain 30 percent of the variation in the output of the non-R&D sector. Technology innovations jointly explain most of the variation of output in the R&D sector and 78 percent of the variation of output in the rest of the economy.